Morningness and Conscientiousness: A Meta-analysis, Online Survey and Resting fMRI Study - Debore Buzoku; Sahar Esmat; Ray Norbury (Journal of Circadian Rhythms)
Morningness is associated with several positive health outcomes and personality traits such as conscientiousness. In the current report, meta-analysis demonstrated a significant association between morningness and conscientiousness, data that are consistent with previous meta-analyses. Further, survey report and resting-state functional Magnetic Resonance Imaging (rs-fMRI, N = 43) indicated that the relationship between morningness and conscientiousness was moderated by functional connectivity with the Default Mode Network (DMN). DMN connectivity has been implicated in a number of cognitive functions and higher connectivity in this network is associated with higher conscientiousness.